Determining the Scope of the Principle of Contractual Freedom in the Light of the Theory of Rule and Right - Ali Mokhtari Chaharbari; Ali Akbar Farahzadi (آموزه‌‌های فقه مدني, 2020)
The limiting factors of the principle of contractual freedom include the laws of mandatory, public order, good morals, and persons cannot compromise unlike them. According to the jurisprudential principles and legal circumstantial legal evidence such as Article 1295 of the Civil Code, public order and good morals must also be found in the laws. Principally, it is not mentioned in the law whether or not the law is complementary (supplementary) or mandatory, and the interpretive opinions of jurists are often not helpful. From the jurisprudential point of view, the nature of the limiting factors of the principle of contractual freedom can be analyzed by the rule and the nature of the supplementary rules with the right. It is not always enough to refer to jurisprudence to determine the right or ruling of the issues agreed upon by individuals. Certainly, the jurists have come up with solutions for recognizing the right and ruling in mistaken cases. According to the jurists in mistaken cases, the principle is neither about the truth of the doubtful case nor its verdict, and according to the principle of non-existence, the existential effects of truth and ruling should be taken away from it and the transportation, transfer, extinctive and agreement against it should be nullified. In this case, due to the similarity of the right and the verdict, if the person wants to have an obligation for the application or omission of the mistaken case, which is their common feature; must consider certainty case; which is the necessary conditions for commitment to the principle of permission and authorization. The result of the execution of the principle and the mentioned way of agreeing on the mistaken case is not the principle of complementary (supplementary) or mandatory but rather indicating the matter between the two things that are doubtful.